Responsi Siswa Terhadap e-modul Biologi Terintegrasi Nilai – Nilai IMTAQ pada Materi Invertebrata - Dinda Putri Afifah; Siti Robiah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to determine students' responses to the biology e-module integrated with IMTAQ values ​​in the Invertebrate material that was developed. This research is R&D research that uses the modified ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. This research is limited to the Development stage. The sample was determined using purposive sampling technique, and the sample size was 65 students from three schools, namely SMAN 1 Pekanbaru, SMAN 5 Pekanbaru and SMAS PGRI Pekanbaru. Data collection uses student response sheets and analysis uses descriptive techniques. The research results obtained an average of 85.87% from the three schools and were included in the